Seismic cable restrainer design method to control the large-displacement response for multi-span simply supported bridges crossing fault rupture zones. Issue 149 (October 2021) - Zhang, Fan; Li, Shuai; Zhao, Taiyi; Wang, Jingquan
Abstract: Previous earthquakes have highlighted the seismic vulnerability of fault-crossing multi-span simply supported (FC-MSSS) bridges due to the large displacement of decks. Restraining devices, being of low cost and easy to install, can be a potential alternative to prevent the large displacement or falling of bridge spans for FC-MSSS bridges. However, the current restrainer design guidelines cannot provide an appropriate design method for such restraining devices in MSSS bridges accounting for the effect of faulting-induced permanent ground dislocation. To address this issue, this study aims to propose a restrainer design procedure for FC-MSSS bridges. In this proposed procedure, the restrainers are designed according to the combination of response spectrum analysis based on a linearized 2-degree-of-freedom (2-DOF) analytical model and quasi-static analysis of the bridge. A five-span simply supported bridge crossing Puqian-Qinglan fault, which is located in Puqian Bay in Hainan, China, is chosen as a case study. Two types of restrainers, i.e., elastic steel and superelastic shape memory alloy (SMA) cables, are considered for the fault-crossing bridge. Over 30 synthetic ground motions with increasing permanent ground dislocations are generated using a hybrid simulation approach. Numerical studies show that the restrainers designed by the proposed method could efficiently limit the relative displacement within a designer-specified value for the fault-crossing bridges. Using SMA cables as seismic restrainers could noticeably reduce the required length compared with elastic steel cables. Highlights: A new restrainer design method is proposed for the fault-crossing bridges. Faulting-induced permanent ground dislocation is considered for the design method. The design method was evaluated using parametric numerical analyses. Both elastic and superelastic restrainers can effectively control the large-displacement for fault-crossing bridges.